Pengaruh Inovasi Produk Dan Promosi Terhadap Peningkatan Penjualan Pada Depot Air Niki Fress - Dedy Faizal Saputra; Semuel Batlajery; Muhammad Awal; Aldisa Arifudin (Musamus University, Merauke Papua Indonesia., 2024)
This research aims to find out the influence of product innovation and promotion on increasing sales at the Niki Fress Merauke Water Depot. The approach used in this research is a quantitative approach and uses multiple linear regression analysis with the tools used for this research, namely SPSS version 26. The population in this research is all customers and visitors at the Niki Fress Merauke Water Depot with a sample of 96 people. The results of the multiple linear regression analysis that have been processed produce the equation Y = 1.363 + 0.716(X1) + 0.220(X2) + e. From the results of hypothesis testing, namely the t test and F test, it shows that the Product Innovation and Promotion variables have a partial and simultaneous influence and significance on increasing sales at the Niki Fress Merauke Water Depot. This is proven by the tcount value being greater than ttable, namely 6.102 > 1.661. The sig value in the table is 0.000 because the sig is less than 0.05, which shows that Product Innovation (X1) has a significant influence. Thus Ha is accepted and H0 is rejected. The t-calculated value of Promotion (X2) is greater than t table, namely 1.760 > 1.661. The sig value in the table is 0.000 because sig is less than 0.05, which shows that Promotion has a significant influence. Thus Ha is accepted and H0 is rejected. Then Fcount is 41.419 > Ftable is 3.09. with a significance level of 0.000 < 0.05 so that Ha is accepted and H0 is rejected. then it shows that the variables Product Innovation (X1) and Promotion (X2) together or simultaneously have a significant effect on the variable Sales Increase (Y). The Adjusted R Square value is 0.540, where all independent variables together influence the increase in sales at the Niki Fress Merauke Water Depot by 54% while the remaining 46% is influenced by other variables not examined in this research.